Systemic Dosing of Thymosin Beta 4 before and after Ischemia Does Not Attenuate Global Myocardial Ischemia-Reperfusion Injury in Pigs - Stark, Christoffer K.-J.; Tarkia, Miikka; Kentala, Rasmus; Malmberg, Markus; Vähäsilta, Tommi; Savo, Matti; Hynninen, Ville-Veikko; Helenius, Mikko; Ruohonen, Saku; Jalkanen, Juho; Taimen, Pekka; Alastalo, Tero-Pekka; et al. (Frontiers in Pharmacology, 2016)
The use of cardiopulmonary bypass and aortic cross-clamping causes myocardial ischemia-reperfusion injury and can lead to reduced postoperative cardiac function. We investigated whether this injury could be attenuated by thymosin beta 4, a peptide which has showed cardioprotective effects. Pigs received either thymosin beta 4 or placebo and underwent cardiopulmonary bypass and aortic cross-clamping for 60 minutes with cold intermittent blood-cardioplegia and were then followed for 30 hours. Myocardial function and blood flow was studied by cardiac magnetic resonance and PET imaging. Tissue and plasma samples were analyzed to determine the amount of cardiomyocyte necrosis and apoptosis as well as pharmacokinetics of the peptide. In vitro studies were performed to assess its influence on blood coagulation and vasomotor tone. Serum levels of the peptide were increased after administration compared to control samples. Thymosin beta 4 did not decrease the amount of cell death. Cardiac function and global myocardial blood flow was similar between the study groups. At high doses a vasoconstrictor effect on mesentery arteries and a vasodilator effect on coronary arteries was observed and blood clot firmness was reduced when tested in the presence of an antiplatelet agent. Despite promising results in previous trials the cardioprotective effect of thymosin beta 4 was not demonstrated in this model for global myocardial ischemia-reperfusion injury.